Budget Deficit and Fiscal Administration in Selected Sub-Saharan African Countries - Ezinando, Emenike Edwin Ekenechukwu; Jeroh, Edirin (Vysoké učení technické v Brně, Fakulta podnikatelská, 2017)
Purpose: An examination of budget performance’ relationship with fiscal administration in selected countries of sub-saharan Africa is the thrust of this study. Secondary data from 12 countries in Sub-Saharan Africa (SSA) for the period (2002- 2016) was sought and analysed. Methodology/methods: Analytical tools deployed for statistical analysis include the Ordinary Least Square (OLS) regression method, correlation analysis, variance inflation factor (VIF) tests for multicollinearity, and Breusch-Pagan/Cook Weisberg test for heteroskedasticity. 5% level of test of significance was employed to measure the altitude of statistical association between all variables. Scientific aim: Efforts were made to empirically ascertain by means of available statistics the relationship between budget deficits and fiscal administration in SSA. Findings: Indications from this study implied that countries SSA recorded trends of significant levels of revenue decline and fiscal balances have deteriorated despite the various acclaimed adjustments in the expenditures profiles by governments in the region. Also a significant relationship was found between budget deficit and fiscal administration among countries in SSA. Conclusion: Since budget deficit has remained a recurring decimal in SSA, countries in the region have resorted to high reliance on borrowed funds to finance the increasing amounts of budget deficits; the consequence being the exposure of countries in SSA to high cost of borrowing.
Keywords: Budgeting; Fiscal Deficit; Taxation; Revenue Generation; Government Expenditure; Sub-Saharan Africa